2015
DOI: 10.1016/j.carbon.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of graphene on Cu (1 0 0) and (1 1 1) surfaces

Abstract: We present results of molecular dynamics simulations of graphene on Cu surfaces. Interactions were modelled with the Charge Optimized Many Body potential, which gives a reasonable though not flawless description of the graphene--Cu system. The interaction between Cu and complete graphene sheets is characterized by an 'averaged out' interaction at a large bonding distance.Many bonding characteristics are indifferent to the details of how the Cu surface atoms are arranged, including the surface orientation and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 50 publications
(44 reference statements)
3
31
1
Order By: Relevance
“…Especially, the introduction of dihedral interaction terms in the COMB3 potential can capture the delocalized bonding and bond bending during the CVD process on a particular substrate. The wrinkle formation due to the size mismatch of graphene and Cu-substrate has been studied using COMB3 potential, which was comparable to experimental results 98 . This potential was also used to understand the role of growth parameters such as absorption energy, migration barrier, and temperature in the Cu deposition on ZnO substrate 131 .…”
Section: For Details)supporting
confidence: 71%
See 1 more Smart Citation
“…Especially, the introduction of dihedral interaction terms in the COMB3 potential can capture the delocalized bonding and bond bending during the CVD process on a particular substrate. The wrinkle formation due to the size mismatch of graphene and Cu-substrate has been studied using COMB3 potential, which was comparable to experimental results 98 . This potential was also used to understand the role of growth parameters such as absorption energy, migration barrier, and temperature in the Cu deposition on ZnO substrate 131 .…”
Section: For Details)supporting
confidence: 71%
“…The REBO and AIREBO potentials are used to simulate the CVD process and growth of 2D amorphous carbon on substrates, mechanical properties of MoS 2 , and even study the thermal stability of C 60 2D nanostructures 97 . The COMB3 potentials have been used to simulate the experimental CVD deposition and growth of graphene and metal on substrates 98 . The ReaxFF potentials have been used to explore the structures of several 2D materials under intercalation, study the defects and groups on the surfaces of MXene materials, simulate CVD growth of MoS 2 layers, and explore the synthesis of 2D polymeric materials in experiments 7,99 .…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“… 34 who recently concluded that kinks they observed in graphite were due to buckling, and with Klaver et al . 35 who used atomistic simulations to explain why when graphene layers-deposited on Cu at high temperatures-were cooled, single surface wrinkles, that were quite mobile, formed as a result of buckling.…”
mentioning
confidence: 99%
“…where E2D is the tensile rigidity (2.12 × 10 3 eV/nm 2 [24]) and G is the graphene-copper adhesion energy per area (3.28 eV/nm 2 [17]), and the second equality comes from substituting E2D and G in the equation. h will be the distance between graphene and substrate and it can be written as…”
Section: Computational Detailsmentioning
confidence: 99%